Impact of extreme temperatures on emergency hospital admissions by age and socio-economic deprivation in England. (September 2022) - Rizmie, Dheeya; de Preux, Laure; Miraldo, Marisa; Atun, Rifat
Abstract: Climate change poses an unprecedented challenge to population health and health systems' resilience, with increasing fluctuations in extreme temperatures through pressures on hospital capacity. While earlier studies have estimated morbidity attributable to hot or cold weather across cities, we provide the first large-scale, population-wide assessment of extreme temperatures on inequalities in excess emergency hospital admissions in England. We used the universe of emergency hospital admissions between 2001 and 2012 combined with meteorological data to exploit daily variation in temperature experienced by hospitals (N = 29, 371, 084). We used a distributed lag model with multiple fixed-effects, controlling for seasonal factors, to examine hospitalisation effects across temperature-sensitive diseases, and further heterogeneous impacts across age and deprivation. We identified larger hospitalisation impacts associated with extreme cold temperatures than with extreme hot temperatures. The less extreme temperatures produce admission patterns like their extreme counterparts, but at lower magnitudes. Results also showed an increase in admissions with extreme temperatures that were more prominent among older and socioeconomically-deprived populations - particularly across admissions for metabolic diseases and injuries. Highlights: The first evidence of extreme temperature on inequalities in hospital use in England. Emergency hospital utilisation increased across the elderly and deprived populations. Vulnerable populations were less protected from health inequalities related to weather. The results underscore the value of mitigation strategies for weather variability.